Assessment of the Effect of Pyrimethamine, a Potent Inhibitor of Multidrug and Toxin Extrusion Protein 1/2K, on the Pharmacokinetics of Gefapixant (MK‐7264), a P2X3 Receptor Antagonist. Issue 1 (19th June 2021) - Nussbaum, Jesse C.; Hussain, Azher; Ma, Bennett; Min, K. Chris; Evers, Raymond; Li, Yun; Garrett, Graigory; Stoch, S. Aubrey; Iwamoto, Marian
Abstract: Gefapixant (MK‐7264, AF‐219) is a first‐in‐class P2X3 antagonist in development for refractory or unexplained chronic cough. Gefapixant is primarily cleared by renal excretion. To assess the importance of the multidrug and toxin extrusion protein 1 (MATE1) and MATE2K transporters in the elimination of gefapixant, a drug‐drug interaction study was conducted evaluating the effect of coadministration of a single dose of pyrimethamine, a competitive inhibitor of MATE1 and MATE2K, on the single‐dose pharmacokinetics of gefapixant in healthy participants. Safety and tolerability were also assessed. In this open‐label, 2‐period, fixed‐sequence study, a 45‐mg dose of gefapixant was administered to 12 participants in period 1. After a 7‐day washout, a 50‐mg dose of pyrimethamine was administered 3 hours before a 45‐mg dose of gefapixant in period 2. Compared with the administration of gefapixant alone, concomitant dosing of gefapixant with pyrimethamine increased the total gefapixant plasma exposure (area under the plasma concentration–time curve from time 0 to infinity) by 24%, reduced gefapixant renal clearance by 30%, and increased gefapixant mean terminal half‐life from 7.7 to 10.3 hours. The most frequently reported adverse events were dysgeusia, hypogeusia, and dry mouth; all adverse events were considered of mild intensity and resolved by the end of the study. These results support that MATE1 and/or MATE2K contribute to the renal clearance of gefapixant, but the effect of inhibition of these transporters on gefapixant pharmacokinetics is not considered clinically meaningful.